Metode Mengajar Rasulullah Saw: (Kajian Pedagogis-Sosiologis) - Alya Dinia Asyfiqi Masykur; Syamsurizal Yazid (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to describe the teaching method of the Prophet Muhammad SAW. From pedagogical and sociological studies. This study uses a qualitative approach with a library research method. The results of this study indicate that the teaching method of the Prophet Muhammad SAW is a perfect example in educating and conveying Islamic teachings. The teaching method of the Prophet Muhammad SAW. Including by example, teaching in stages, through advice, dialogue and questions and answers, parables, demonstrations, and rewards and punishments. Pedagogically, the teacher is a source of values, of course he is a person who must always be obeyed and followed, while the obligation of students is to respect their teachers, sociologically, education should form good morals, and provide skills and knowledge that are useful in everyday life. Soft skill development is highly prioritized in the process of a person's education. Keywords: teaching methods, pedagogical, sociological